1990
DOI: 10.1159/000261850
|View full text |Cite
|
Sign up to set email alerts
|

Acoustics and Phonology of Complex Tone Sandhi

Abstract: This paper presents a detailed acoustic and auditory description of the kind of complex tone sandhi found in the Northern Wu dialects of Chinese. Mean fundamental frequency, amplitude and duration values from many tokens of 1 native speaker of Zhenhai dialect are used to show how the acoustical characteristics of the 6 citation tones can be related to the 20 different forms in disyllabic lexical sandhi. Three phonetically motivated processes are demonstrated in this relationship: stress effects; paradigmatic r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

1996
1996
2024
2024

Publication Types

Select...
4
3
3

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(8 citation statements)
references
References 3 publications
1
7
0
Order By: Relevance
“…Stress that is independent of morphosyntactic structure has also been reported in Chinese dialects, and its relation to tone sandhi has been an uncomfortable one in the study of Chinese tone. For example, Rose (1990) reported that in the Northern Wu dialect Zhenhai, disyllabic words with MH or H on the first syllable have initial stress, whereas those with ML or L on the first syllable have final stress; this stress pattern was confirmed by native speaker perception. The tone sandhi pattern in Zhenhai, however, is not easily predicted by this stress pattern, and Li (2003, 2005) showed that a good understanding of the pattern can only be achieved when we carefully tease apart the interaction between this tonally induced stress and initial prominence, which provides the initial syllable with a longer duration.…”
Section: Directions For Chinese Tone Researchmentioning
confidence: 89%
“…Stress that is independent of morphosyntactic structure has also been reported in Chinese dialects, and its relation to tone sandhi has been an uncomfortable one in the study of Chinese tone. For example, Rose (1990) reported that in the Northern Wu dialect Zhenhai, disyllabic words with MH or H on the first syllable have initial stress, whereas those with ML or L on the first syllable have final stress; this stress pattern was confirmed by native speaker perception. The tone sandhi pattern in Zhenhai, however, is not easily predicted by this stress pattern, and Li (2003, 2005) showed that a good understanding of the pattern can only be achieved when we carefully tease apart the interaction between this tonally induced stress and initial prominence, which provides the initial syllable with a longer duration.…”
Section: Directions For Chinese Tone Researchmentioning
confidence: 89%
“…The overall approach in this tone analysis follows the methodology of prior tonetics research, such as Edmondson et al (2004), Rose (1987, 1990, 1991, 1993, 1994, 1997), and Zhu (1999), where tone syllable tokens are normalized for time duration and then compared using mean pitch values at selected relative time points. Because the total duration of a tone varies between speakers and also varies between tokens of a single speaker, a necessary first step is to normalize the time duration.…”
Section: Methodology For Data Collectionmentioning
confidence: 99%
“…Tone extension is irrelevant. Zhenhai (Rose (1990), Li (2005)), a Northern Wu dialect spoken in northeast Zhejiang Province, furnishes another example of default insertion in both directions. The tonal inventory on unchecked syllables in Zhenhai is HL, MH, ML, and LM.…”
Section: Default Insertion In Both Directionsmentioning
confidence: 99%